Culture, Power, and Political Change: Skeptics and the Civil Sphere. (April 2015) - Bedingfield, Sid
This essay argues that Jeffrey C. Alexander's civil sphere theory provides a useful new tool for those who study mass communication and its role during times of political change. In a functioning democracy, Alexander maintains, the feelings of solidarity that emanate from a shared cultural legacy can shape political outcomes and foster social change. This essay responds to skeptics who claim Alexander's theory minimizes the impact of raw power in politics and thus presents a Utopian view of civil society. It contends that civil sphere theory can enhance the study of power, particularly the role powerful forces play in shaping the cultural contests that animate democratic life and lay the foundation for political and social change.